The formation of surface multilayers at the air-water interface from sodium diethylene glycol monoalkyl ether sulfate/AlCl3 solutions: the role of the alkyl chain length. - Xu, H; Penfold, J; Thomas, R; Petkov, J; Tucker, I; Webster, J (2013)
The influence of the alkyl chain length on surface multilayer formation at the air-water interface for the anionic surfactant sodium diethylene glycol monoalkyl ether sulfate, SAE2S, in the presence of Al(3+) multivalent counterions, in the form of AlCl3, is described. In the absence of electrolyte, the saturated monolayer adsorption is determined by the headgroup geometry and is independent of the alkyl chain length. In the presence of Al(3+) counterions, surface multilayer formation occurs, due to the strong SAE2S/Al(3+) binding and complexation. The neutron reflection data show that the alkyl chain length of the surfactant has a significant impact upon the evolution of the surface multilayer structure with surfactant and AlCl3 concentration. Increasing the alkyl chain length from decyl to tetradecyl results in the surface multilayer formation occurring at lower surfactant and AlCl3 concentrations. At the short alkyl chain lengths, decyl and dodecyl, the regions of multilayer formation with a small number of bilayers are increasingly extended with decreasing alkyl chain length. For the alkyl chain lengths of tetradecyl and hexadecyl, the surface behavior is further affected by decreases in the surfactant solubility in the presence of AlCl3, and this ultimately dominates the surface behavior at the longer alkyl chain lengths.